Reduced ATP turnover during hibernation in relaxed skeletal muscle - Cosimo De Napoli; Luisa Schmidt; Mauro Montesel; Laura Cussonneau; Samuele Sanniti; Lorenzo Marcucci; Elena Germinario; Jonas Kindberg; Alina Lynn Evans; Guillemette Gauquelin-Koch; Marco Narici; Fabrice Bertile; et al. (Nature Communications)
Abstract Hibernating brown bears, due to a drastic reduction in metabolic rate, show only moderate muscle wasting. Here, we evaluate if ATPase activity of resting skeletal muscle myosin can contribute to this energy sparing. By analyzing single muscle fibers taken from the same bears, either during hibernation or in summer, we find that fibers from hibernating bears have a mild decline in force production and a significant reduction in ATPase activity. Single fiber proteomics, western blotting, and immunohistochemical analyses reveal major remodeling of the mitochondrial proteome during hibernation. Furthermore, using bioinformatical approaches and western blotting we find that phosphorylated myosin light chain, a known stimulator of basal myosin ATPase activity, is decreased in hibernating and disused muscles. These results suggest that skeletal muscle limits energy loss by reducing myosin ATPase activity, indicating a possible role for myosin ATPase activity modulation in multiple muscle wasting conditions.